Characterization of PDC6, a third structural gene for pyruvate decarboxylase in Saccharomyces cerevisiae. - Hohmann, S (1991)
Pyruvate decarboxylase is the key enzyme in alcoholic fermentation in yeast. Two structural genes, PDC1 and PDC5 have been characterized. Deletion of either of these genes has little or no effect on the specific pyruvate decarboxylase activity, but enzyme activity is undetectable in mutants lacking both PDC1 and PDC5 (S. Hohmann and H. Cederberg, Eur. J. Biochem. 188:615-621, 1990). Here I describe PDC6, a gene structurally closely related to PDC1 and PDC5. The product of PDC6 does not seem to be required for wild-type pyruvate decarboxylase activity in glucose medium; delta pdc6 mutants have no reduced specific enzyme activity, and the PDC6 deletion did not change the phenotype or the specific enzyme activity of mutants lacking either or both of the other two structural genes. However, in cells grown in ethanol medium the PDC6 deletion caused a reduction of pyruvate decarboxylase activity. Northern (RNA) blot analysis showed that PDC6 is weakly expressed, and expression seemed to be higher during growth in ethanol medium. This behavior remained obscure since pyruvate decarboxylase catalyzes an irreversible reaction. Characterization of all combinations of PDC structural gene deletion mutants, which produce different amounts of pyruvate decarboxylase activity, showed that the enzyme is also needed for normal growth in galactose and ethanol medium and in particular for proper growth initiation of spores germinating on ethanol medium.